Child Care Subsidies, Quality, and Optimal Income Taxation - Spencer Bastani; Sören Blomquist; Luca Micheletto (Center for Economic Studies and ifo Institute (CESifo), 2017)
In this paper we examine the desirability of subsidizing child care expenditures in a model where parents can choose both the quantity and the quality of child care services they purchase in the market. Our vehicle of analysis is a Mirrleesian optimal tax framework where child care services not only enable parents to work, but also contribute to children's formation of human capital. In addition, there are externalities related to the parents' choice of child care arrangements for their offspring. Using a quantitative simulation model calibrated to the US economy, we evaluate the relative merits of some the most common forms of child care subsidies (tax deductions, tax credits, and opting-out public provision schemes) in terms of their effectiveness in alleviating the distortions associated with income taxation and increasing the quality of child care chosen by parents.
Keywords: H21; H41; 330; optimal income taxation; child care subsidies; tax deductibility; tax credit; public provision of private goods